An ANP-Based Practical Quality Model for a Secure Embedded System with Sensor Network - Hwa-Young Jeong; Jong Hyuk Park; Young-Sik Jeong (International Journal of Distributed Sensor Networks)
The process of creating secure embedded systems with sensor network is highly challenging and complex, particularly from a technical viewpoint. A secure embedded system is used for a specific purpose and operation, and needs hardware-software codesign methodology. As such, there are many considerations in terms of system design when the system developer creates or constructs a secure embedded system with sensor network. However, there is a lack of research into quality models in the area of secure embedded systems in sensor network. This paper seeks to redress this issue by presenting a quality model for a secure embedded system with sensor network. Each quality for the secure embedded system is constructed according to DeLone and McLean's success information system, and has subcriteria according to their characteristics. The present research also focuses on making a quality model network which considers the correlation between the qualities' attributes.